SPONTAN İNTRAKRANYAL HİPOTANSİYONA BAĞLI BAŞAĞRISI: İKİ OLGU SUNUMU - CEYHAN DİRİCAN, Ayten and ÖZTÜRK, Musa and ALTUNKAYNAK, Yavuz and AKTAŞ, Fatih and YALÇINER, Betül and YEŞİL, Ulaş and BAYBAŞ, Sevim (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Spontaneous intracranial hypotension is a syndrome which the orthostatic headache is the main symptom. Characteristically, headache appears in upright position or deteriorates, while it improves or completely recovers in lying position. Diagnosis and treatment are rather important since, although rarely encountered, it may lead to complications which may cause to vital risk. Observation.- In this article, 2 cases diagnosed with SIH ( one male and one female) are presented for the reason that these cases bear the typical specifications of this rarely met syndrome. It will be appropriate to think of SIH syndrome which quite seldom observed and to make the researches this syndrome oriented especially for the patients applying with the complaint of headache with postural features.